Social factors of mental illness ( A field study in Erbil Psychiatric Hospital) - احمد, د. زەریا احمد طاهر (Sulaimani Journal for Humanities, 2025)
Today, mental illness is an important issue in the world in general, whether in human life, social life, relationships and family, the achievements of academic life to the fields of religion, economy, culture of nations. This study is a qualitative study using state research tool. It is obvious that mental illness is very widespread and diverse nowadays. The aim of this study is to identify the most important social factors of mental illness, including social, family and occupational factors that contribute to the development of this disease. The sample used in this study are patients who visited Erbil Psychiatric Hospital whether temporarily or longer stay. (10) patients (5) women and (5) men were recruited through personality research, ie using personality method and using interviews and observations. During this study, more than one factor caused mental illness, including poor economic conditions, family breakdown, failure to study and work, unemployment, housing, societal values and customs and how family behavior towards children Whether through violence or excessive pampering, marital infidelity, lack of justice between children and other reasons.